Tourists' strategies: an acculturation approach - Rasmi, Sarah; Ng, Siew Imm; Lee, Julie Anne; Soutar, Geoff N. (Elsevier, 2014)
Acculturation theory has been widely used to understand and explain migrant and sojourner adaptation. However, it has yet to be examined in a tourist context. We extended the literature by evaluating the applicability of Berry's (1997) bidimensional acculturation model to a sample of 668 recent and prospective international travelers from China (n = 205), Germany (n = 201), and the United States (n = 262). Our results suggested that the acculturation model can be extended to tourist contexts and used for segmentation purposes. Specifically, tourists' acculturation strategies were associated with their preferences for home culture maintenance and host culture immersion, as well as behavioral, holiday, and activity preferences. Ethnocentrism and uncertainty avoidance were also found to vary as a function of tourists' acculturation strategy.